Opioid substitution treatment, relapse and addiction-related outcomes in prison setting and after release: A longitudinal study - Geißelsöder, Kerstin; Weiss, Maren; Boksán, Klara; Dechant, Michael; Endres, Johann; Breuer, Maike; Stemmler, Mark; Wodarz, Norbert (Nordic Studies on Alcohol and Drugs, 2024)
Aims: Opioid addiction is a common problem among prisoners. The aim of this study was to examine differences between people who are incarcerated receiving opioid substitution treatment (OST) and those not receiving OST on addiction-related outcome variables during incarceration and after release from prison. Variables covered illicit use of opioids, non-prescribed substitution medication and other substances, opioid withdrawal symptoms, opioid craving, non-fatal overdoses and post-release substitution treatment. Design: Interviews (European Addiction Severity Index, EuropASI) were conducted with 247 participants in German prisons before release. Participants were interviewed again 1 month and 3–6 months after release from prison. Results: During incarceration, participants who received OST used less illicit opioids and non-prescribed substitution medication than those who did not receive OST. After release from prison, participants in the OST group reported less illicit opioid use and less non-prescribed substitution medication use, as well as less opioid craving. Participants who received OST in prison were more likely to be in OST at post-release follow-up than those who had not received in-prison OST. Conclusion: OST appears to have a positive effect on illicit opioid use and craving both in prison and after release, as well as on treatment at follow-up, which can be considered a protective factor.
Created from Fastlane, Scopus look-up
Keywords: opioid addiction; opioid substitution treatment; prison